The VATLY Radio Telescope - Hiep, Nguyen Van; Anh, Pham Tuan; Diep, Pham Ngoc; Dong, Pham Ngoc; Hoai, Do Thi; Nhung, Pham Thi Tuyet; Thao, Nguyen Thi; Darriulat, Pierre (Communications in Physics, 2013)
A small radio telescope (SRT) has been installed on the roof of the Hanoi astrophysics laboratory VATLY. It is equipped with a 2.6 m diameter mobile parabolic dish remotely controlled in elevation and azimuth and with super-heterodyne detection around the 21 cm hydrogen line. First results of observations of the Sun and of the centre of the Milky Way are presented. They demonstrate the high quality of the telescope performance and are used to evaluate lobe size, signal to noise ratios, anthropogenic interferences and measurement accuracies. Particular attention is given to the measurement of the pointing accuracy. The rich measurement programme that is now at hand is briefly sketched.